2020
DOI: 10.1101/2020.02.04.933614
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancement of Target Specificity of CRISPR-Cas12a by Using a Chimeric DNA-RNA Guide

Abstract: The CRISPR-Cas9 system is widely used for target-specific genome engineering. Cpf1 is one of the CRISPR effectors that controls target genes by recognizing thymine-rich protospacer adjacent motif (PAM) sequences. Cpf1 has a higher sensitivity to mismatches in the guide RNA than does Cas9; therefore, off-target sequence recognition and cleavage are lower. However, it tolerates mismatches in regions distant from the PAM sequence (TTTN or TTN) in the protospacer, and offtarget cleavage issues may become more prob… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The importance of RNA A-form helical structure and 2′-OH chemistry has been partially investigated for pseudoknot stability and protein interaction 85,86 , but not in the context of CRISPR-Cas systems. The unique noncanonical nature of the Cas12a 5′ pseudoknot, as well as previous attempts at modification 74,78,81 , suggested that it would be challenging to modify for therapeutic development. To focus on the pseudoknot structure and uncouple it from guide region effects, we maintained an entirely native RNA ribose (2′-OH) guide region throughout most of this study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The importance of RNA A-form helical structure and 2′-OH chemistry has been partially investigated for pseudoknot stability and protein interaction 85,86 , but not in the context of CRISPR-Cas systems. The unique noncanonical nature of the Cas12a 5′ pseudoknot, as well as previous attempts at modification 74,78,81 , suggested that it would be challenging to modify for therapeutic development. To focus on the pseudoknot structure and uncouple it from guide region effects, we maintained an entirely native RNA ribose (2′-OH) guide region throughout most of this study.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have used chemical modification to investigate the necessity of the ribose 2′-OH group in the AsCas12a crRNA 5′ pseudoknot structure for enzyme activity. The primary question was whether the pseudoknot structure was too complex or sensitive for efficient chemical modification, which previous studies had suggested 74,78,81 . The rationale for our approach is the high likelihood that therapeutic applications of Cas12a that require direct delivery of the crRNA will also require heavy or complete chemical modification, as is the case for siRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations